Macroanatomic investigations on the innervation of the eye in holstein cattle - Emrullah Eken; Kamil Beşoluk; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
This study was carried out to investigate the origines, courses and innervation areas of the cranial nerves innervating the eye in Holstein cattle. For this purpose, it was used the eight of Holstein cattle ensured from Konya slaughterhouses. The materials were dissected after fixed in formaldehit solution 10 %. It was detected that the involved nerves left the cranial cavity through the different opening after sleming from the different regions ol the brain, then, ended by reaching the concerned innervation parts. The optic nerve left the cranial cavity via the optic canal alter arising Irom the optic chiasma, then, scattered in the retina by going through the optic papilla. The oculomotor nerve went out of the cranial cavity through the foramen orbitorotundum after steming from the crural cerebri and divided into the dorsal and ventral branches. The trochlear nerve left the cranial cavity via the foramen orbitorotundum after originating from the caudal coliculus and terminated in the caudal third of the dorsal obliquus muscle. The ab-ducens nerve exited the cranial cavity through the foramen orbitorotundum by emerging from the medulla oblongata, after I ha I, scattered in the rectus lateralis and retractor muscles.